A cluster of Mycobacterium massiliense keratitis in foundry workers. (April 2016) - Hung, J.H.; Chang, T.C.; Wu, J.J.; Lai, C.C.; Huang, F.C.; Huang, Y.H.
Abstract: Three consecutive workers from the same foundry had Mycobacterium massiliense keratitis. The strains isolated from each patient were identical. This is the first report of a non-surgery-related outbreak of non-tuberculous mycobacterial ocular infection. An investigation revealed that injured cornea with exposure to aerosolized non-tuberculous mycobacteria might account for this outbreak.